Acidosis, cognitive dysfunction and motor impairments in patients with kidney disease. (31st October 2021) - Imenez Silva, Pedro H; Unwin, Robert; Hoorn, Ewout J; Ortiz, Alberto; Trepiccione, Francesco; Nielsen, Rikke; Pesic, Vesna; Hafez, Gaye; Fouque, Denis; Massy, Ziad A; De Zeeuw, Chris I; Capasso, Giovambattista; et al.
ABSTRACT: Metabolic acidosis, defined as a plasma or serum bicarbonate concentration <22 mmol/L, is a frequent consequence of chronic kidney disease (CKD) and occurs in 10–30% of patients with advanced stages of CKD. Likewise, in patients with a kidney transplant, prevalence rates of metabolic acidosis range from 20% to 50%. CKD has recently been associated with cognitive dysfunction, including mild cognitive impairment with memory and attention deficits, reduced executive functions and morphological damage detectable with imaging. Also, impaired motor functions and loss of muscle strength are often found in patients with advanced CKD, which in part may be attributed to altered central nervous system (CNS) functions. While the exact mechanisms of how CKD may cause cognitive dysfunction and reduced motor functions are still debated, recent data point towards the possibility that acidosis is one modifiable contributor to cognitive dysfunction. This review summarizes recent evidence for an association between acidosis and cognitive dysfunction in patients with CKD and discusses potential mechanisms by which acidosis may impact CNS functions. The review also identifies important open questions to be answered to improve prevention and therapy of cognitive dysfunction in the setting of metabolic acidosis in patients with CKD. Graphical Abstract: